Kualitas Pelayanan, Harga, Dan Kepuasan Terhadap Loyalitas Pelanggan Pada Foto Copy Ujung Bulu Uepai - Yunila Yunila; Muhamad Pariama (CV. Aksara Global Akademia, 2024)
This research aims to determine and analyze the influence of service quality, price and satisfaction on customer loyalty at Foto Copy Ujung Bulu Uepai, secondly to find out and analyze the influence of service quality on customer loyalty at Foto Copy Ujung Bulu Uepai, third to find out and analyze the influence of price on customer loyalty on Ujung Bulu Uepai Photo Copy and further to find out and analyze the influence of satisfaction on customer loyalty on Ujung Bulu Uepai Photo Copy. The sampling technique used in research is opportunity sampling, where the sample is determined based on chance and anyone who happens to meet the researcher and is deemed suitable as a data source can be used as a sample. The results of this research are: Based on the results of the data analysis that has been obtained, it can be concluded that the variables of service quality, price and satisfaction simultaneously and partially have a positive and significant effect on customer loyalty at Ujung Bulu Uepai Photo Copy.